Removable Dentures of Modern Dentistry - Vakhidova, Kurbanova Nodira (American Journal of Bioscience and Clinical Integrity, 2024)
Removable prosthesis is still not a thing of the past – it continues to be widely used in dentistry. A modern removable prosthesis is a compact, convenient product that allows you to quickly restore the aesthetics and functionality of the dentition. Removable and conditionally removable prosthetics are an excellent solution if it is impossible to install non-removable prostheses.